2021
DOI: 10.1101/2021.08.27.457992
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SNR-efficient distortion-free diffusion relaxometry imaging using ACcelerated Echo-train shifted EPTI (ACE-EPTI)

Abstract: Purpose: To develop an efficient acquisition technique for distortion-free diffusion MRI and diffusion-relaxometry. Methods: A new ACcelerated Echo-train shifted Echo-Planar Time-resolved Imaging (ACE-EPTI) technique is developed to achieve high-SNR, distortion- and blurring-free diffusion and diffusion-relaxometry imaging. ACE-EPTI employs a newly designed variable density spatiotemporal encoding with self-navigation capability, that allows submillimeter in-plane resolution using only 3-shot. Moreover, an ech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…This may again be related to the fact that the hybrid fibre orientations are more directly related to myelinated axons, where myelinsensitive microscopy is typically used to characterise fibre fanning patterns ex vivo, and where dendrites complicate dMRI modelling at the grey-white matter boundary. Whether the results can be extrapolated to in vivo data needs further investigation, for example using recently proposed high-resolution dMRI protocols such as Romer-EPTI which is able to acquire submm resolution in an achievable scan time 58 . Considering the global volume difference between humans and macaques (macaque brain volume is ~1/12 of the human brain volume), the spatial resolutions we used (1mm, 0.6mm and 0.4mm) are approximately equivalent to the 2.5, 1.5, and 1 mm in humans, roughly corresponding to resolutions achievable in the clinic, in typical research data and among the highest achievable resolution so far.…”
Section: Discussionmentioning
confidence: 99%
“…This may again be related to the fact that the hybrid fibre orientations are more directly related to myelinated axons, where myelinsensitive microscopy is typically used to characterise fibre fanning patterns ex vivo, and where dendrites complicate dMRI modelling at the grey-white matter boundary. Whether the results can be extrapolated to in vivo data needs further investigation, for example using recently proposed high-resolution dMRI protocols such as Romer-EPTI which is able to acquire submm resolution in an achievable scan time 58 . Considering the global volume difference between humans and macaques (macaque brain volume is ~1/12 of the human brain volume), the spatial resolutions we used (1mm, 0.6mm and 0.4mm) are approximately equivalent to the 2.5, 1.5, and 1 mm in humans, roughly corresponding to resolutions achievable in the clinic, in typical research data and among the highest achievable resolution so far.…”
Section: Discussionmentioning
confidence: 99%
“…The original multi-shot EPTI (ms-EPTI) mostly targets anatomical imaging and high spatial resolution applications. For example, it has been demonstrated to provide high efficiency for fast multi-contrast imaging (47,48), multi-parametric quantitative MRI (49,50), high-resolution functional MRI (51), highresolution distortion-free diffusion imaging (52)(53)(54), and myelin water imaging (55).…”
Section: Introductionmentioning
confidence: 99%
“…Ning et al 21 proposed a similar framework and introduced a simplified method, named REDIM, to estimate the joint moments of relaxation and diffusion coefficients. We note that the coupling between T 1 , T2 relaxation time and diffusivity have also been investigated to characterize tissue microstructure 22–26 . For example, Melbourne et al 24 and Slator et al 25 demonstrated the feasibility of combined diffusion and T 2 or T2 relaxation MRI on placenta for separating signals from fetal and maternal circulations, and identifying dysfunction, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…We note that the coupling between T 1 , T * 2 relaxation time and diffusivity have also been investigated to characterize tissue microstructure. [22][23][24][25][26] For example, Melbourne et al 24 and Slator et al 25 demonstrated the feasibility of combined diffusion and T 2 or T * 2 relaxation MRI on placenta for separating signals from fetal and maternal circulations, and identifying dysfunction, respectively. Benjamini et al 23 investigated combined T 1 -T 2 -diffusion changes linked to diffuse axonal injury caused by trauma in the human brain.…”
Section: Introductionmentioning
confidence: 99%